La enseñanza de las lenguas profesionales y académicas - Rodríguez-Piñero Alcalá, Ana Isabel (Círculo de Lingüística Aplicada a la Comunicación, 2013)
Teaching professional and academic languages. The knowledge society, globalization, migration phenomena, information and communication technologies (ICTs) are all relevant factors both in relation to the description of specialised languages and to their acquisition and teaching. New approaches in teaching-learning processes are demanded by the framework of the European Space of Higher Education, due to the profound changes taking place in university education. The main goal of this article is to provide an overview of the main current teaching methods and techniques when designing a language course for professional and academic purposes.